Strategic Leaderhip-A Case Study in Engineering Education Scenario - Johri, Arpita; Sharma, Sanjay Kumar (Journal of Engineering Education Transformations, 2025)
This research paper deals with a case study of Strategic Leadership that has shown colossal growth in terms of University results as well as the team spirit. This case study is of B.Tech First Year Team of ABES Engineering College, Ghaziabad, UP, for last two sessions 2014-15&2015-16. The team is still growing, but is on a roll!